A budget impact analysis of rapid human immunodeficiency virus screening in Veterans Administration emergency departments. - Gidwani, Risha; Goetz, Matthew Bidwell; Kominski, Gerald; Asch, Steven; Mattocks, Kristin; Samet, Jeffrey H; Justice, Amy; Gandhi, Neel; Needleman, Jack (The Journal of emergency medicine, 2012)
Human immunodeficiency virus (HIV) screening is cost-effective and recommended in populations with low disease prevalence. However, because screening is not cost-saving, its financial feasibility must be understood.
Keywords: AIDS Serodiagnosis; Emergency Service, Hospital; Health Care Costs; HIV Infections; Hospitals, Veterans; Humans; Mass Screening